An Assessment of Hygiene Maintenance Factors Effect on Employeesâ Productivity in Nigerian Telecommunication Industry - Ogbo, Ann; Anthony, Kifordu Anyibuofu; Kosisochukwu, Okagu (International Research Journal of Management, IT & Social Sciences, 2017)
The study aimed at establishing an assessment of hygiene maintenance factors effects on employeesâproductivity. The hygiene/maintenance factors play vital role in employeesâ productivity. They do not motivate employee in organization, yet they must be present or dissatisfaction will arise. . The study is aimed to pursue the following objectives: To determine the extent to which working conditions improve the performance of employees, to ascertain the effect of interpersonal relations within the organization on firmsâ profitability and to assesthe extent to whichcompensation improve the performance of employees.The study was conducted using the survey approach. The geographical scope of the study was Mobile telecommunication network (MTN), located within Enugu metropolis. Two sources of data were utilized in the study: they included primary and secondary sources. The primary source wasthrough the administration of copies of designed questionnaire to a total of forty one respondents that made up the sample size for the study.